2021
DOI: 10.1017/s1368980021000434
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling food insecurity and maternal depression: which comes first?

Abstract: Objective: To determine the temporal directionality of the association between food insecurity and maternal depression. Design: Food insecurity was measured at two time points using the 18-item USDA Food Security Scale. Maternal depression was measured at two time points using the 15-item Composite International Diagnostic Interview-Short Form. Two structural equation models were utilized to evaluate the impact of food insecurity on maternal depression (model 1) and the impact of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…motor skills enable the child to interact with the environment and this interaction is required by the child to develop proper language skills (43) . Second, HFI can compromise parental well-being, including maternal mental health (7,(44)(45)(46) , and interferes with parent-child interactions and the emotional environment at home (47,48) , which may lead to delays in ECD due to poor interaction between child and caregivers (7,8) . In summary, the nutrition-and psycho-emotional stress related to HFI may lead to a lack of responsive and stimulating care by caregivers (37,49) , limiting early stimulation and learning opportunities needed for proper child development, including activities such as talking to children, telling stories, playing and well-supervised explorations of environments outside the home (50) .…”
Section: Discussionmentioning
confidence: 99%
“…motor skills enable the child to interact with the environment and this interaction is required by the child to develop proper language skills (43) . Second, HFI can compromise parental well-being, including maternal mental health (7,(44)(45)(46) , and interferes with parent-child interactions and the emotional environment at home (47,48) , which may lead to delays in ECD due to poor interaction between child and caregivers (7,8) . In summary, the nutrition-and psycho-emotional stress related to HFI may lead to a lack of responsive and stimulating care by caregivers (37,49) , limiting early stimulation and learning opportunities needed for proper child development, including activities such as talking to children, telling stories, playing and well-supervised explorations of environments outside the home (50) .…”
Section: Discussionmentioning
confidence: 99%
“…Related, mothers in Class 1 report greater material hardships compared to mothers in Class 4, even though Class 1 mothers had several protective socio-economic factors: higher percent of mothers with income 200–299% of the FPL (working poor), educated and employed. Material hardships, partner incarceration, depressive/anxious symptoms, and substance use have been independently linked to lower food insecurity risk [ 9 , 29 , 31 , 34 , 37 ]. Even though the mothers in high employment hardship and low-income class (Class 4) were similar to Classes 1, 2 and 3 in poverty, mothers in Class 4 were more likely to report being married or cohabitating and engaged in a higher use of WIC, which may also explain their lower risk of food insecurity compared to mothers in other high-risk classes [ 59 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding concurs with the Healthy Immigrant Effect, where immigrants display better health than individuals from host country [ 69 ]. Prior research has shown that poor health and substance use behaviors may limit mother’s financial stability and the ability to maintain steady employment [ 70 ] placing the family at risk of experiencing food insecurity and other material hardships [ 9 , 37 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Additionally, stress, depression, and anxiety are more common among food insecure mothers, 14,15 and research has suggested a bidirectional relationship between maternal depression and food insecurity. 16…”
Section: Introductionmentioning
confidence: 99%